Whole-Exome Sequencing Identifies Pathogenic Variants in TJP1 Gene Associated With Arrhythmogenic Cardiomyopathy. (October 2018) - De Bortoli, Marzia; Postma, Alex V.; Poloni, Giulia; Calore, Martina; Minervini, Giovanni; Mazzotti, Elisa; Rigato, Ilaria; Ebert, Micaela; Lorenzon, Alessandra; Vazza, Giovanni; Cipriani, Alberto; Bariani, Riccardo; et al.
Abstract : Background: Arrhythmogenic cardiomyopathy (ACM) is an inherited cardiac disease characterized by progressive fibro-fatty myocardial replacement, ventricular arrhythmia, heart failure, and sudden death. Causative mutations can be identified in 60% of patients, and most of them are found in genes encoding mechanical junction proteins of the intercalated disk. Methods: Whole-exome sequencing was performed on the proband of an ACM family. Sanger sequencing was used to screen for mutations the tight junction protein 1 ( TJP1 ) gene in unrelated patients. Predictions of local structure content and molecular dynamics simulations were performed to investigate the structural impact of the variants. Results: A novel c.2006A>G p.(Y669C) variant in TJP1 gene was identified by whole-exome sequencing in a patient with ACM. TJP1 encodes zonula occludens 1, an intercalated disk protein interacting with proteins of gap junctions and area composita. Additional rare TJP1 variants have been identified in 1 of 40 Italian probands (c.793C>T p.(R265W)) with arrhythmogenic right ventricular cardiomyopathy and in 2 of 43 Dutch/German patients (c. 986C>T, p.(S329L) and c.1079A>T, p.(D360V)) with dilated cardiomyopathy and recurrent ventricular tachycardia. The p.(D360V) variant was identified in a proband also carrying the p.(I156N) pathogenic variant in DSP . All 4 TJP1 variants are predicted to be deleterious and affect highly conserved amino acids, either at the GUK (guanylate kinase)–like domain (p.(Y669C)) or at the disordered region of the protein between the PDZ2 and PDZ3 domains (p.(R265W), p.(S329L), and p.(D360V)). The local unfolding induced by the former promotes structural rearrangements of the GUK domain, whereas the others are predicted to impair the function of the disordered region. Furthermore, rare variants in TJP1 are statistically enriched in patients with ACM relative to controls. Conclusions: We provide here the first evidence linking likely pathogenic TJP1 variants to ACM. Prevalence and pathogenic mechanism of TJP1 -mediated ACM remain to be determined. Abstract : Supplemental Digital Content is available in the text.